2023
DOI: 10.1371/journal.pone.0281338
|View full text |Cite
|
Sign up to set email alerts
|

An internet-based self-applied rat phobia treatment using a Virtual Therapy Assistant: Study protocol for a randomized controlled trial

Abstract: Specific phobias are a common anxiety disorder that deteriorates the lives of people who suffer from them. To reduce the symptoms produced by this mental disorder exposure therapies have been used. However, low- and middle-income countries, including Mexico, have the lowest rate of treatment due to multiple barriers that prevent addressing mental health problems. Self-applied treatments have been explored in previous studies, nevertheless, high dropout rates are a common problem in this kind of treatment. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Both studies which were found to have a VRE lacking ludic immersion potential involve non-interactive 360 • videos. In one of the studies, the feasibility of a multimodal internet-based exposure approach is evaluated, incorporating images, videos, games, and 360 • videos [64]. While the entire intervention holds potential for ludic immersion, particularly during the digital game phase, the only VR component is present when the user watches 360 • videos, which were not described as possessing the characteristics associated with ludic immersion.…”
Section: No Potential For Ludic Immersionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies which were found to have a VRE lacking ludic immersion potential involve non-interactive 360 • videos. In one of the studies, the feasibility of a multimodal internet-based exposure approach is evaluated, incorporating images, videos, games, and 360 • videos [64]. While the entire intervention holds potential for ludic immersion, particularly during the digital game phase, the only VR component is present when the user watches 360 • videos, which were not described as possessing the characteristics associated with ludic immersion.…”
Section: No Potential For Ludic Immersionmentioning
confidence: 99%
“…Many studies with low potential for spatial immersion shared a similar type of navigation freedom, limited to three degrees of movement where users could only rotate their heads in the virtual environment but not move within it [59,60,[64][65][66][67]71,75,81]. Although Farrell et al [67] and Minns et al [65] had high realism due to high-definition video captures of real environments and animals, they lacked sufficient navigational freedom as they were non-interactive videos that didn't allow users to explore the presented environment spatially.…”
Section: Low Potential For Spatial Immersionmentioning
confidence: 99%
See 1 more Smart Citation